PENGARUH PENGELUARAN KONSUMSI DAN INVESTASI PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Darma Rika Swaramarinda; Susi Indriani (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
ABSTRACT This research was aimed at describing connections between government expenditures to Indonesia's economic growth in the period 1997-2007. In this research, central government expenditure can be divided into current expenditure and capital expenditure. The data were taken from Badan Pusat Statistik, International Funding Statistik (IFS) and Asian Development Bank (ADB). The analysis use qualitative and quantitative. Qualitative analysis described in descriptive about government expenditures in Indonesia. The quantitative analysis used Ordinary Least Squares (OLS) with secondary data. The Regression of research results show that: (1) current expenditure has a positive relationship to economic growth and the effect statistically significant. (2) capital expenditure has a positive relationship to economic growth and the effect statistically significant. Keywords: government expenditure, current expenditure, capital expenditure, economic growth